Analisis Metode Penilaian Persediaan Terhadap Keefektifan Pengendalian Persediaan pada PD. Tiana - B1033131009, Hary Gunawan (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
The role of inventory is very important so must be extra careful especially when dealing with merchandise inventory valuation method. Therefore, the aim of this research is to determine the impact of inventory valuation method to the effectiveness of inventory control in PD. Tiana. This research use a qualitative descriptive approach. Source data used are primary data and secondary data. Sources of Data Obtained through the study documentation and literature assessment. The methods of analysis used is qualitative descriptive analysis method. Based on the results of research concluded that the implementation of the inventory valuation method in controlling inventory in PD. Tiana is quite effective. Although using two methods of inventory, but does not affect the reporting of the value of inventory in the financial statements. Keywords: Merchandise Inventory, Inventory Valuation Method, The Effectiveness of Inventory Control.